P49 A genome-wide association study of hepatic encephalopathy in chronic liver disease. (28th September 2020) - Manimaran, Sylvia; Goh, Ee Teng; McQuillin, Andrew; Atkinson, Stephen R; Morgan, Marsha Y; Thursz, Mark R
Abstract : Introduction: Hepatic encephalopathy (HE) is a frequent complication of cirrhosis but its development is not inevitable. There is evidence, from candidate gene studies, that the propensity to develop HE may be genetically determined but the findings are inconsistent. The aim of this study was to undertake a GWAS of HE in chronic liver disease. Methods: Genomic DNA was available in 857 participants in the UK STOPAH alcoholic hepatitis trial and 120 participants in the Royal Free Hospital (RFH) HE surveillance study. All had chronic liver disease and the majority were of British/Irish ancestry. Information on HE status was available in 777 participants in STOPAH and 109 in the RFH cohort. Cases were defined in the STOPAH cohort as those presenting with/developing overt HE (OHE) within 28 days of admission based on West Haven criteria, and in the RFH cohort on a combination of West Haven criteria, the PHES test and EEG theta frequency. Controls were defined as STOPAH participants who did not present/develop OHE within 28 days and in the RFH cohort as participant classified as neuropsychiatrically unimpaired or as having minimal HE. Samples were genotyped using three different SNP arrays (Illumina core exome chip, Psych Chip and OmniExpress array). Separate GWAS analyses were undertaken of each array using Plink (v1.9) followed by meta-analysis in METAL (v1.5.0). The primary analysis was adjusted first for population stratification and second for age, sex, and model for end-stage liver disease (MELD) score. Linear regression association analysis was also conducted in the RFH cohort (n=111) using the additional HE defining variables. Results: A total of 206 (26.5%) of the STOPAH participants and 33 (30.3%) of the RFH cohort had OHE. Single variants in TMEM135 (Transmembrane Protein 135), CACNB2 ( Calcium Voltage-Gated Channel Auxiliary Subunit Beta 2 ), and WBP2 (WW Domain Binding Protein 2) showed suggestive association (P < 1 × 10 -5 ) with OHE in the primary analysis; the association with TMEM135, was retained in the adjusted analyses. An association at genome-wide significance (P=3.73 × 10 -8 ) was identified between the PHES score and a variant lying at a genetic locus containing genes AMTN (Amelotin) and MUC7 (Mucin 7, Secreted ), the gene of interest. Conclusions: TMEM135 influences key metabolic pathways involved in the pathophysiology of HE, namely oxidative stress and glutamine and glutamate homeostasis. MUC7 influences factors which result in a reduction in systemic inflammation and influences the gut microbiota. These interesting associations need further exploration in extended cohorts.